THE IMPLEMENTATION OF THE 2013 CURRICULUM IN LEARNING ACTIVITIES CONDUCTED BY THE ENGLISH TEACHER OF FIRST GRADE AT JUNIOR HIGH SCHOOL 17 MAKASSAR - Kurniawan A. (Universitas Islam Negeri Alauddin Makassar, 2015)
The objectives of this research were to know how the implementation of the 2013 curriculum in learning activity conducted by the English teacher, and to find out the teacher’s difficulties in implementing it. In collecting data about the implementation of the 2013 curriculum in learning activity conducted by the English teacher, the researcher conducted observation. The data about the teacher’s difficulties was achieved by conducting interview. The subject of this research was English teachers of first grade at Junior High School 17 Makassar. The data achieved by observing about the implementation of the 2013 curriculum in learning activity conducted by the English teachers showed that there were a lot of activities conducted by the English teachers in learning activity. They were observing questioning, experimenting, associating, and communicating. Those activities were conducted step by step. The data achieved by interviewing about the teachers’ difficulties in implementing the 2013 curriculum showed that there were a lot of teachers’ difficulties. The difficulties faced by the teacher A and the teacher B were affective appraisal, the lack of time in explaining materials, the lack of learning facilities, and the students handbook. Based on the data above, the researcher concluded that the implementation of the 2013 curriculum conducted by the English teachers of first grade at Junior High School 17 Makassar was in accordance with the government policy. Giving affective appraisal and the student handbook were the teachers’ difficulties generally.